Mobility scooters in Italy: the reason of a “missed revolution”. A potential resource for individual mobility in the Covid-19 era needs legislation - Cannata, Giuseppe; Nigro, Marialisa; Ljoka, Concetta; Murè, Mihaela; Coluccia, Guerino; Giordani, Laura; Crisalli, Umberto; Foti, Calogero (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Mobility scooters have evolved up to modern cabin versions and to application of still futuristic solutions in the automotive sector: they could even be a resource for individual mobility in the Covid-19 era, but in Italy they seem unable to establish, mainly because of lacking and approximate legislation. Article 46 of the Italian Highway Code generically delegates the definition of “machines for disabled persons” (not considered vehicles) to “current Community provisions”, but the explanatory note of heading 8713 of EU Combined Nomenclature of goods and EU Regulations 718/2009 and 2021/1367 equate mobility scooters to motor vehicles: as such they are an unknown entity for the Highway Code, therefore they should be considered unregulated atypical vehicles, which are forbidden in public areas. We propose the classification of mobility scooters as “motor vehicles” for both able and disabled persons and a specific regulation of their characteristics and circulation. Our legislative proposal could be useful even outside Italy, since some disputes at the European and National Courts and the absence of mobility scooters among the three-wheel vehicles and quadricycles categorized by EU Regulation 168/2013 are a symptom that they are still a controversial topic even abroad and need a clear-cut national and international legislation.